Comparison of Performance from Green Bonds and Conventional Bonds Traded on the Indonesia Stock Exchange - Wiliya Wiliya; Dwi Susanti; Sukono Sukono (International Journal of Business, Economics, and Social Development, 2021)
Bonds are types of securities in the form of a debt acknowledgment letter for loan money from the public in a certain form, but with a minimum tenor of three years and promise of interest rewards in which the amount and payment have been determined in advance. Looking at the current global problems regarding degradation of environmental equality and climate change, bonds were developed where the proceeds of issuance were exclusively applied to finance environmentally friendly projects, is green bonds. However, the issuance of green bonds in Indonesia is slight. This research aims to find out the comparison of individual performance of green bonds and conventional bonds traded on the Indonesia Stock Exchange. The method used to measure performance is Sharpe Ratio. The result indicates that performance of green bond worse than conventional bond. This research can be used as a consideration for investor in making investment based on performance.